2017
DOI: 10.1021/acs.inorgchem.6b02606
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Cyclopentadienyl Molybdenum Compounds towards Formic Acid: Structural Characterization of CpMo(PMe3)(CO)2H, CpMo(PMe3)2(CO)H, [CpMo(μ-O)(μ-O2CH)]2, and [Cp*Mo(μ-O)(μ-O2CH)]2

Abstract: The molecular structures of CpMo(PMe)(CO)H and CpMo(PMe)(CO)H have been determined by X-ray diffraction, thereby revealing four-legged piano-stool structures in which the hydride ligand is trans to CO. However, in view of the different nature of the four basal ligands, the geometries of CpMo(PMe)(CO)H and CpMo(PMe)(CO)H deviate from that of an idealized four-legged piano stool, such that the two ligands that are orthogonal to the trans H-Mo-CO moiety are displaced towards the hydride ligand. While CpMo(PMe)(CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 139 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…The crystallographic Mo-Mo distances on the other hand are slightly shorter than twice Pauling's covalent bond radius for Mo (1.371 Å). At 2.676 and 2.648 Å, respectively, they are in the range of distances expected for a Mo-Mo single or double bond (Pauling and Kamb, 1986; Shin and Parkin, 1998; Neary and Parkin, 2017). Both diamond cores are to some extent asymmetric: the molybdenum ions in 1 dia have different bond lengths with the bridging nitrogen atoms (Mo 1 -N 1, 2 : 1.850 Å, Mo 2 -N 1, 2 : 1.964 Å), whereas each molybdenum in 2 dia has two different bond lengths with the nitrogen bridges (1.892, 1.927 Å) (Keane et al, 2015; Duman et al, 2016).…”
Section: Resultsmentioning
confidence: 73%
“…The crystallographic Mo-Mo distances on the other hand are slightly shorter than twice Pauling's covalent bond radius for Mo (1.371 Å). At 2.676 and 2.648 Å, respectively, they are in the range of distances expected for a Mo-Mo single or double bond (Pauling and Kamb, 1986; Shin and Parkin, 1998; Neary and Parkin, 2017). Both diamond cores are to some extent asymmetric: the molybdenum ions in 1 dia have different bond lengths with the bridging nitrogen atoms (Mo 1 -N 1, 2 : 1.850 Å, Mo 2 -N 1, 2 : 1.964 Å), whereas each molybdenum in 2 dia has two different bond lengths with the nitrogen bridges (1.892, 1.927 Å) (Keane et al, 2015; Duman et al, 2016).…”
Section: Resultsmentioning
confidence: 73%
“…The decarboxylation of formic acid is of much current interest with respect to its ability to serve as a hydrogen storage material, and there is particular emphasis on the use of earth abundant nonprecious metals to catalyze the release of hydrogen. In this regard, we previously demonstrated that Ni­(PMe 3 ) 4 is able to effect catalytic release of H 2 from formic acid at 80 °C. ,, We have now demonstrated that the heteroleptic variant, (dppbz)­Ni­(PMe 3 ) 2 , is also capable of such activity, with a turnover number of 10 over a period of ca. 16 h at 60 °C; however, the activity diminishes considerably after this period, and analysis of the reaction by 1 H NMR spectroscopy demonstrates that the reaction is accompanied by the formation of Ni­(dppbz) 2 and (dppbz)­Ni­(PMe 3 )­(CO).…”
Section: Results and Discussionmentioning
confidence: 99%